BNF 74 : September 2017 - March 2018. - British Medical Association; Royal Pharmaceutical Society of Great Britain (London : BMJ Group : Pharmaceutical Press, 2017)
This biannual publication provides details on all medicines currently available on the UK market, with particular reference to their uses, contraindications, side effects, dosage and relative cost.
Includes index.
"Published under the authority of a Joint Formulary Committee"--Preface.
Keywords: Medicine -- Formulae, receipts, prescriptions; Great Britain; Pharmacology -- Great Britain; Drugs -- Prescribing -- Great Britain; MEDICAL -- Pharmacology; Health and Fitness; Drugs -- Prescribing; Medicine